A kind of degradable corrugated board glue and its preparation process

Through the combination of modified starch and flame retardant, the problem of corrugated cardboard is easily absorbed and flammable, and it provides high water resistance and flame retardant degradable glue, which improves the adhesion and safety of corrugated cardboard. In various application scenarios.

CN117820987BActive Publication Date: 2024-12-13SHANDONG RONGTAI PACKAGING CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410005677.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-03
Publication Date
2024-12-13
Estimated Expiration
2044-01-03

AI Technical Summary

Technical Problem

Corrugated cardboard is easy to absorb water and flammable. Traditional adhesives have poor water resistance, insufficient adhesion ability, and are non-degradable, which poses fire safety hazards.

Method used

Modified starch and modified flame retardant are used to improve the water resistance and flame retardant properties of the glue through nucleophilic substitution reaction, radical polymerization and crosslinking treatment, and form a dense mesh structure to enhance adhesion and flame retardant effect.

Benefits of technology

It provides degradable corrugated cardboard glue with excellent bonding properties, water resistance and flame retardant properties. It is widely used in packaging, home decoration and other fields, reducing the fire safety risks of corrugated cardboard.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004646931730000111
    Figure BDA0004646931730000111
Patent Text Reader

Abstract

The invention discloses a degradable corrugated board glue and a preparation process thereof. The corrugated board glue prepared by the present invention includes the following raw materials by weight: 80-100 parts of modified starch, 4-6 parts of acrylamidopropyltrimethoxysilane, 2-3 parts of modified flame retardant, 8-12 parts of sodium hydroxide, 0.5-2 parts of defoamer, 1.5-2.5 parts of plasticizer, 200-300 parts of ethanol solution, and 2-3 parts of stabilizer. The degradable corrugated board glue provided by the present invention uses starch with biodegradable characteristics and natural renewable ability as the main raw material, and is modified. The glue prepared based on the present invention has excellent bonding performance, water resistance, flame retardancy and degradability, and the corrugated board prepared by the present invention can be widely used in packaging, home decoration, billboards, etc.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glue, and in particular to degradable corrugated board glue and a preparation process thereof. Background Art

[0002] Corrugated cardboard is a paper composite board, a non-metallic sandwich material with viscoelastic-elastic properties. It is made of corrugated corrugated core paper and inner and outer paper. It is used to make various corrugated boxes, paper pallets, paper pads, paper corner protectors, display racks, paper furniture, paper toys, lightweight building materials, etc., and has broad prospects. However, the surface of corrugated cardboard is extremely easy to absorb water. Corrugated boxes that are damp may become unusable. In addition, the main component of corrugated cardboard is plant cellulose, which dehydrates and oxidizes as the temperature rises when heated. The oxygen index of corrugated cardboard at room temperature is only 15%. A large number of corrugated boxes are piled up, which poses a great fire safety hazard and is easy to cause fires. Corrugated cardboard adhesive is the most important material in the production process of corrugated cardboard and cartons. Almost all quality indicators of cardboard and cartons are related to adhesives. Therefore, the role of adhesives is very critical. Traditional corrugated cardboard adhesives are easy to absorb moisture, have poor water resistance, poor bonding ability, are non-degradable, and do not have flame retardant properties.

[0003] In order to solve the above problems, it is necessary to develop an adhesive with good water resistance, good bonding performance, biodegradability and flame retardancy to meet higher market demands and application requirements. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a degradable corrugated board glue and a preparation process thereof.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A degradable corrugated board glue comprises the following raw materials by weight: 80-100 parts of modified starch, 4-6 parts of acrylamidopropyltrimethoxysilane, 2-3 parts of modified flame retardant, 8-12 parts of sodium hydroxide, 0.5-2 parts of defoamer, 1.5-2.5 parts of plasticizer, 200-300 parts of ethanol solution, and 2-3 parts of stabilizer;

[0007] The mass ratio of ethanol to deionized water in the ethanol solution is 8:2;

[0008] The modified starch is prepared by the following steps:

[0009] Step A1, add 5-aminoisophthalic acid to dimethylacetamide and stir to mix evenly, then lower the temperature of the solution to 0°C, add triethylamine and stir to mix evenly, then slowly drop acryloyl chloride into the mixture, and stir to react at low temperature. After the dropwise addition is completed, place the mixture in an oil bath, and slowly increase the temperature to 55-75°C, and react at this temperature for 4-8h. After the reaction is completed, pour the mixture into a beaker of 200mL deionized water at 10°C, vacuum filter, wash the filter cake twice with 100mL deionized water at 80-90°C, and place it in a vacuum drying oven at 100°C to dry for 8-12h to obtain product 1;

[0010] Furthermore, the usage ratio of 5-aminoisophthalic acid, dimethylacetamide, triethylamine and acryloyl chloride is 0.2-0.4 mol: 50-150 mL: 7-21 mL: 0.2-0.4 mol.

[0011] Step A2, mixing sodium dodecyl sulfate in deionized water and keeping the mixture at 50°C for 10 minutes, then adding product 1 and stirring to obtain mixed solution 1, then adding starch to 0.5 mol / L hydrochloric acid, stirring in a constant temperature water bath at 60°C for 1 hour, adjusting the pH to 4.0, then raising the temperature of the mixed solution to 70°C, adding two-thirds of ammonium persulfate and stirring to obtain mixed solution 1 dropwise for 1-2 hours, then adding the remaining ammonium persulfate and reacting for 2-3 hours. After the reaction is completed, the modified starch is obtained;

[0012] Further, the dosage ratio of starch, hydrochloric acid, ammonium persulfate and mixed solution 1 is 3-6 g: 5.5-11 mL: 0.045-0.09 g: 1.5-3 mL, and the dosage ratio of sodium dodecyl sulfate, deionized water and product 1 in mixed solution 1 is 0.06-0.12 g: 15-30 mL: 0.25-0.45 g;

[0013] Furthermore, the starch includes any one of corn starch, wheat starch, tapioca starch, and potato starch.

[0014] The modified flame retardant is prepared by the following steps:

[0015] Step B1, add (3-aminopropyl)trimethoxysilane, triethylamine and diphenyl ether into a reactor, slowly add phenylphosphonic dichloride with a dropping funnel under nitrogen conditions, and always keep the system temperature ≤50°C. After the addition is completed, the system temperature is raised to 160-180°C for reaction for 4 hours. After the reaction is completed, filter with suction, then add water to dissolve the filter cake and adjust the pH to 8 under constant stirring, filter with suction again, wash, and vacuum dry at 80°C for 12 hours to obtain a flame retardant precursor;

[0016] Furthermore, the usage ratio of (3-aminopropyl)trimethoxysilane, triethylamine, diphenyl ether and phenylphosphonic dichloride is 0.025-0.045 mol: 1.5-3.0 g: 50-100 mL: 0.01-0.02 mol.

[0017] Step B2, under nitrogen conditions, add boric acid and 1,2-dichloroethane into a reactor, raise the temperature to 45-55°C and stir to mix evenly, then add the flame retardant precursor solution dropwise into the reactor through a constant pressure dropping funnel, raise the temperature to 80-90°C and react for 7-9h after the reaction is completed, filter the mixed solution, rotary evaporate the precipitate, and place the precipitate at 50°C under vacuum and dry for 12h to obtain a modified flame retardant;

[0018] Furthermore, the amount ratio of boric acid, 1,2-dichloroethane and flame retardant precursor solution is 0.92-2.78g:20-60mL:30-90mL, and the flame retardant precursor solution is prepared by stirring and mixing the flame retardant precursor and 1,2-dichloroethane in an amount ratio of 7.19-21.56g:30-90mL.

[0019] A method for preparing degradable corrugated board glue comprises the following steps:

[0020] Weigh the raw materials by weight, stir acrylamidepropyltrimethoxysilane in an ethanol solution for 5 minutes to obtain a premix, then heat the modified starch to 60-70°C, and slowly add the premix and sodium hydroxide and stir to react for 30 minutes. After the reaction is completed, add the modified flame retardant, defoamer, plasticizer and stabilizer and stir to react for 30-60 minutes. After the reaction is completed, a degradable corrugated cardboard glue is obtained.

[0021] Beneficial effects of the present invention:

[0022] The degradable corrugated board glue provided by the invention uses starch with biodegradable characteristics and natural renewable ability as the main raw material, and the starch is modified. The glue prepared by using the starch has excellent bonding performance, water resistance, flame retardancy and degradability. The corrugated board prepared by using the starch can be widely used for packaging, home decoration, billboards and the like.

[0023] In starch modification: First, the nucleophilic substitution reaction between the amino group in 5-aminoisophthalic acid and the acyl chloride group in acryloyl chloride is used to synthesize product 1, and the double bond structure contained in it can undergo free radical polymerization in the subsequent reaction. Secondly, starch free radicals can be generated in the presence of the initiator ammonium persulfate. With the addition of product 1, the starch free radicals will attack the C=C bond in product 1. At the same time, the -COOH on the product 1 molecule will undergo an esterification reaction with the -OH in the starch molecule. The new chemical bonds will continuously replace the original hydrogen bonds, thereby increasing the cohesion of the starch, thereby hindering the invasion of water molecules and improving the water resistance of the starch. Finally, acrylamide propyl trimethoxysilane is used as a crosslinking agent. The amide group and C=C bond contained in it can be grafted and crosslinked with the modified starch molecules to form a dense network crosslinking structure, further preventing the entry of water molecules and improving the water resistance of starch glue; the siloxane contained in it is hydrolyzed to generate silanol groups, which may also react with the hydroxyl groups in starch and the free carboxyl groups in modified starch. The molecular reinforcement structure formed can also enhance the interaction between glue and corrugated paper, thereby further improving the water resistance of glue. In addition, the introduction of product 1 and the crosslinking agent destroys the original smooth surface of starch particles, making the particle surface rough, improving the bonding force between glue and corrugated paper, and having better bonding strength.

[0024] In the modified flame retardant: first, a flame retardant precursor is synthesized by the reaction between (3-aminopropyl)trimethoxysilane and phenylphosphonic dichloride, thereby introducing three flame retardant elements N, P, and Si, and the siloxane structure contained therein can participate in subsequent reactions; secondly, the siloxane contained in the flame retardant precursor is hydrolyzed to generate a silanol bond, which can react with the hydroxyl group in boric acid, thereby introducing the B element on the basis of the flame retardant precursor. The N and P elements contained in the modified flame retardant will produce non-flammable NH3 and phosphorus-containing free radicals during the combustion of the matrix, which will inhibit the continued combustion of the matrix by diluting the concentration of oxygen and flammable volatiles through non-flammable gases, creating a blow-out effect, and capturing active H· and OH· free radicals; a dense carbon layer structure will be generated, which can isolate oxygen and inhibit heat transfer, thereby preventing the carbon layer from continuing to oxidize and burn; in addition, the free silanol and boric acid molecules in the modified flame retardant can also react with starch molecules and active groups in modified starch to form a cross-linked structure, so that the modified flame retardant can play a flame retardant role in the matrix more lastingly and effectively, avoiding the problems of traditional small molecule flame retardants being easy to precipitate and volatilize in the matrix. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] 1) Modified starch is prepared by the following steps:

[0028] Step A1, add 5-aminoisophthalic acid to dimethylacetamide and stir to mix evenly, then reduce the temperature of the solution to 0°C, add triethylamine and stir to mix evenly, then slowly add acryloyl chloride to the mixture, and stir to react at low temperature. After the addition is completed, place the mixture in an oil bath, and slowly increase the temperature to 55°C, and react at this temperature for 4 hours. After the reaction is completed, pour the mixture into a beaker of 200mL deionized water at 10°C, vacuum filter, wash the filter cake twice with 100mL deionized water at 80°C, and place it in a vacuum drying oven at 100°C to dry for 8 hours to obtain the product 1,5-aminoisophthalic acid, dimethylacetamide, triethylamine and acryloyl chloride in an amount ratio of 0.2mol:50mL:7mL:0.2mol;

[0029] Step A2, mix sodium dodecyl sulfate in deionized water and keep it at 50°C for 10 minutes, then add product 1 and stir and mix evenly to obtain mixed solution 1, then add starch to 0.5 mol / L hydrochloric acid, stir in a constant temperature water bath at 60°C for 1 hour, adjust the pH to 4.0, then increase the temperature of the mixed solution to 70°C, add two-thirds of ammonium persulfate and stir and mix evenly, add mixed solution 1 dropwise, drip it for 1 hour, then add the remaining ammonium persulfate, react for 2-3 hours, after the reaction is completed, the modified starch is obtained, the amount ratio of starch, hydrochloric acid, ammonium persulfate and mixed solution 1 is 3g:5.5mL:0.045g:1.5mL, the amount ratio of sodium dodecyl sulfate, deionized water and product 1 in mixed solution 1 is 0.06g:15mL:0.25g, and the starch is corn starch.

[0030] 2) The modified flame retardant is prepared by the following steps:

[0031] Step B1, add (3-aminopropyl) trimethoxysilane, triethylamine and diphenyl ether into a reactor, slowly add phenylphosphonic dichloride with a dropping funnel under nitrogen conditions, and always keep the system temperature ≤50°C. After the addition is completed, the system temperature is raised to 160°C for reaction for 4 hours. After the reaction is completed, filter with suction, then dissolve the filter cake in water and adjust the pH to 8 under constant stirring, filter and wash again, and vacuum dry at 80°C for 12 hours to obtain a flame retardant precursor, the amount ratio of (3-aminopropyl) trimethoxysilane, triethylamine, diphenyl ether and phenylphosphonic dichloride is 0.025mol:1.5g:50mL:0.01mol;

[0032] Step B2, under nitrogen conditions, add boric acid and 1,2-dichloroethane to the reactor, raise the temperature to 45 ° C and stir to mix evenly, then add the flame retardant precursor solution dropwise to the above reactor through a constant pressure dropping funnel, after the addition is completed, raise the temperature to 80 ° C and react for 7 hours, after the reaction is completed, filter the mixed solution, rotary evaporate the precipitate, and place the precipitate at 50 ° C under vacuum and dry for 12 hours to obtain a modified flame retardant, the amount ratio of boric acid, 1,2-dichloroethane and flame retardant precursor solution is 0.92g: 20mL: 30mL, and the flame retardant precursor solution is prepared by stirring and mixing the flame retardant precursor and 1,2-dichloroethane in an amount ratio of 7.19g: 30mL.

[0033] Example 2

[0034] 1) Modified starch is prepared by the following steps:

[0035] Step A1, add 5-aminoisophthalic acid to dimethylacetamide and stir to mix evenly, then lower the temperature of the solution to 0°C, add triethylamine and stir to mix evenly, then slowly drop acryloyl chloride into the mixture, and stir to react at low temperature. After the dropwise addition is completed, place the mixture in an oil bath, and slowly increase the temperature to 65°C, and react at this temperature for 6 hours. After the reaction is completed, pour the mixture into a beaker of 200mL deionized water at 10°C, vacuum filter, wash the filter cake twice with 100mL deionized water at 85°C, and place it in a vacuum drying oven at 100°C to dry for 10 hours to obtain the product 1,5-aminoisophthalic acid, dimethylacetamide, triethylamine and acryloyl chloride in an amount ratio of 0.3mol:100mL:14mL:0.3mol;

[0036] Step A2, sodium dodecyl sulfate is mixed evenly in deionized water and kept at 50°C for 10 minutes, then product 1 is added and stirred to obtain mixed solution 1, starch is then added to 0.5 mol / L hydrochloric acid, and stirred in a constant temperature water bath at 60°C for 1 hour, the pH is adjusted to 4.0, and then the temperature of the mixed solution is increased to 70°C, two-thirds of ammonium persulfate is added and stirred to obtain mixed solution 1, and the mixed solution 1 is added dropwise for 1.5 hours, and then the remaining ammonium persulfate is added and reacted for 2.5 hours. After the reaction is completed, modified starch is obtained, and the amount ratio of starch, hydrochloric acid, ammonium persulfate and mixed solution 1 is 4.5 g: 8 mL: 0.06 g: 2.4 mL, the amount ratio of sodium dodecyl sulfate, deionized water and product 1 in the mixed solution 1 is 0.09 g: 23 mL: 0.35 g, and the starch is cassava starch.

[0037] 2) The modified flame retardant is prepared by the following steps:

[0038] Step B1, (3-aminopropyl) trimethoxysilane, triethylamine and diphenyl ether are added to the reactor, and phenylphosphonic acid dichloride is slowly added dropwise with a dropping funnel under nitrogen conditions, and the system temperature is always kept ≤50°C. After the addition is completed, the system temperature is raised to 170°C for reaction for 4 hours. After the reaction is completed, suction filtration is performed, and then the filter cake is dissolved in water and the pH is adjusted to 8 under constant stirring, and suction filtration and washing are performed again, and vacuum drying is performed at 80°C for 12 hours to obtain a flame retardant precursor, and the dosage ratio of (3-aminopropyl) trimethoxysilane, triethylamine, diphenyl ether and phenylphosphonic acid dichloride is 0.035 mol: 2.2 g: 75 mL: 0.015 mol;

[0039] Step B2, under nitrogen conditions, add boric acid and 1,2-dichloroethane to the reactor, raise the temperature to 50°C and stir to mix evenly, then add the flame retardant precursor solution dropwise to the above reactor through a constant pressure dropping funnel, raise the temperature to 85°C and react for 8h, after the reaction is completed, filter the mixed solution, rotary evaporate the precipitate, and place the precipitate at 50°C under vacuum and dry for 12h to obtain a modified flame retardant, the amount ratio of boric acid, 1,2-dichloroethane and flame retardant precursor solution is 1.86g:40mL:60mL, and the flame retardant precursor solution is prepared by stirring and mixing the flame retardant precursor and 1,2-dichloroethane in an amount ratio of 14.37g:60mL.

[0040] Example 3

[0041] 1) Modified starch is prepared by the following steps:

[0042] Step A1, add 5-aminoisophthalic acid to dimethylacetamide and stir to mix evenly, then reduce the temperature of the solution to 0°C, add triethylamine and stir to mix evenly, then slowly add acryloyl chloride to the mixture, and stir to react at low temperature. After the addition is completed, place the mixture in an oil bath, and slowly increase the temperature to 75°C, and react at this temperature for 8 hours. After the reaction is completed, pour the mixture into a beaker of 200mL deionized water at 10°C, vacuum filter, wash the filter cake twice with 100mL deionized water at 90°C, and place it in a vacuum drying oven at 100°C to dry for 12 hours to obtain the product 1,5-aminoisophthalic acid, dimethylacetamide, triethylamine and acryloyl chloride in an amount ratio of 0.4mol:150mL:21mL:0.4mol;

[0043] Step A2, mix sodium dodecyl sulfate in deionized water and keep it at 50°C for 10 minutes, then add product 1 and stir and mix evenly to obtain mixed solution 1, then add starch to 0.5 mol / L hydrochloric acid, stir in a constant temperature water bath at 60°C for 1 hour, adjust the pH to 4.0, then increase the temperature of the mixed solution to 70°C, add two-thirds of ammonium persulfate and stir and mix evenly, add mixed solution 1 dropwise, drip it for 2 hours, then add the remaining ammonium persulfate, react for 3 hours, after the reaction is completed, the modified starch is obtained, the amount ratio of starch, hydrochloric acid, ammonium persulfate and mixed solution 1 is 6g:11mL:0.09g:3mL, the amount ratio of sodium dodecyl sulfate, deionized water and product 1 in mixed solution 1 is 0.12g:30mL:0.45g, and the starch is corn starch and cassava starch.

[0044] 2) The modified flame retardant is prepared by the following steps:

[0045] Step B1, add (3-aminopropyl) trimethoxysilane, triethylamine and diphenyl ether into a reactor, slowly add phenylphosphonic dichloride with a dropping funnel under nitrogen conditions, and always keep the system temperature ≤50°C. After the addition is completed, the system temperature is raised to 180°C for reaction for 4 hours. After the reaction is completed, filter, then add water to dissolve the filter cake and adjust the pH to 8 under constant stirring, filter again, wash, and vacuum dry at 80°C for 12 hours to obtain a flame retardant precursor, the amount ratio of (3-aminopropyl) trimethoxysilane, triethylamine, diphenyl ether and phenylphosphonic dichloride is 0.045mol:3.0g:100mL:0.02mol;

[0046] Step B2, under nitrogen conditions, add boric acid and 1,2-dichloroethane to the reactor, raise the temperature to 55 ° C and stir to mix evenly, then add the flame retardant precursor solution dropwise to the above reactor through a constant pressure dropping funnel, after the addition is completed, raise the temperature to 90 ° C and react for 9 hours, after the reaction is completed, filter the mixed solution, rotary evaporate the precipitate, and place the precipitate at 50 ° C under vacuum and dry for 12 hours to obtain a modified flame retardant, the amount ratio of boric acid, 1,2-dichloroethane and flame retardant precursor solution is 2.78g: 60mL: 90mL, and the flame retardant precursor solution is prepared by stirring and mixing the flame retardant precursor and 1,2-dichloroethane in an amount ratio of 21.56g: 90mL.

[0047] Example 4

[0048] A method for preparing a degradable corrugated cardboard glue comprises the following steps: 80 parts of the modified starch prepared in Example 1, 4 parts of acrylamidopropyltrimethoxysilane, 2 parts of the modified flame retardant prepared in Example 1, 8 parts of sodium hydroxide, 0.5 parts of tributyl phosphate, 1.5 parts of glycerol, 200 parts of ethanol solution, and 2 parts of sorbitol; the mass ratio of ethanol to deionized water in the ethanol solution is 8:2.

[0049] The raw materials were weighed by weight, acrylamidopropyltrimethoxysilane was stirred in an ethanol solution for 5 minutes to obtain a premix, and then the modified starch prepared in Example 1 was heated to 60° C., and the premix and sodium hydroxide were slowly added and stirred for reaction for 30 minutes. After the reaction was completed, the modified flame retardant prepared in Example 1, tributyl phosphate, glycerol and sorbitol were added and stirred for reaction for 30 minutes. After the reaction was completed, a degradable corrugated cardboard glue was obtained.

[0050] Example 5

[0051] A method for preparing a degradable corrugated cardboard glue comprises the following steps: 90 parts of the modified starch prepared in Example 2, 5 parts of acrylamidopropyltrimethoxysilane, 2.5 parts of the modified flame retardant prepared in Example 2, 10 parts of sodium hydroxide, 1 part of tributyl phosphate, 2 parts of glycerol, 250 parts of ethanol solution, and 2.5 parts of sorbitol; the mass ratio of ethanol to deionized water in the ethanol solution is 8:2.

[0052] The raw materials were weighed by weight, acrylamidepropyltrimethoxysilane was stirred in an ethanol solution for 5 minutes to obtain a premix, and then the modified starch prepared in Example 2 was heated to 65° C., and the premix and sodium hydroxide were slowly added and stirred for reaction for 30 minutes. After the reaction was completed, the modified flame retardant prepared in Example 2, tributyl phosphate, glycerol and sorbitol were added and stirred for reaction for 45 minutes. After the reaction was completed, a degradable corrugated cardboard glue was obtained.

[0053] Example 6

[0054] A method for preparing a degradable corrugated cardboard glue comprises the following steps: 100 parts of the modified starch prepared in Example 3, 6 parts of acrylamidopropyltrimethoxysilane, 3 parts of the modified flame retardant prepared in Example 3, 12 parts of sodium hydroxide, 2 parts of tributyl phosphate, 2.5 parts of glycerol, 300 parts of ethanol solution, and 3 parts of sorbitol; the mass ratio of ethanol to deionized water in the ethanol solution is 8:2.

[0055] The raw materials were weighed by weight, acrylamidopropyltrimethoxysilane was stirred in an ethanol solution for 5 minutes to obtain a premix, and then the modified starch prepared in Example 3 was heated to 70° C., and the premix and sodium hydroxide were slowly added and stirred to react for 30 minutes. After the reaction was completed, the modified flame retardant, defoamer, plasticizer and stabilizer prepared in Example 3 were added and stirred to react for 60 minutes. After the reaction was completed, a degradable corrugated cardboard glue was obtained.

[0056] Comparative Example 1

[0057] This comparative example is a glue, which is different from Example 6 in that the starch is not modified, and the rest is the same.

[0058] Comparative Example 2

[0059] This comparative example is a glue, which is different from Example 6 in that the flame retardant is magnesium hydroxide, and the rest is the same.

[0060] The glue prepared in Examples 4-6 and Comparative Examples 1-2 was tested for performance: Adhesion test: The glue was coated between the layers of corrugated paper, the coating thickness was 50 μm, 50 μm aluminum foil was used as the backing material, and the test was performed according to GB-T2790-1995 standard; Water resistance test: The glue was evenly coated on two pieces of 10 cm × 10 cm corrugated paper, overlapped and pressed, dried in an oven at 80°C for 5 minutes, placed at room temperature for one day and then used, the corrugated paper was soaked in 25°C water, and the time for the paperboard to automatically fall off was observed as the water resistance time; Flame retardancy test: The limiting oxygen index was tested using a limiting oxygen index tester. The test results are shown in Table 1:

[0061] Table 1

[0062]

[0063]

[0064] As can be seen from Table 1, the glue prepared by the present invention uses starch as a raw material, has a certain degree of degradability, and has excellent bonding performance, water resistance and flame retardancy.

[0065] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A degradable corrugated cardboard glue, characterized in that: The following raw materials are included by weight: 80-100 parts of modified starch, 4-6 parts of acrylamidopropyltrimethoxysilane, 3-5 parts of modified flame retardant, 8-12 parts of sodium hydroxide, 0.5-2 parts of defoamer, 1.5-2.5 parts of plasticizer, 200-300 parts of ethanol solution, and 2-3 parts of stabilizer; The modified starch is prepared by the following steps: Step A1, add 5-aminoisophthalic acid to dimethylacetamide and stir to mix evenly, then lower the temperature of the solution to 0°C, add triethylamine and stir to mix evenly, then slowly drop acryloyl chloride into the mixture, and stir to react at low temperature. After the dropwise addition is completed, place the mixture in an oil bath, and slowly increase the temperature to 55-75°C, and react at this temperature for 4-8h. After the reaction is completed, pour the mixture into a beaker of 200mL deionized water at 10°C, vacuum filter, wash the filter cake twice with 100mL deionized water at 80-90°C, and place it in a vacuum drying oven at 100°C to dry for 8-12h to obtain product 1; Step A2, mix sodium dodecyl sulfate in deionized water and keep it at 50°C for 10 minutes, then add product 1 and stir and mix evenly to obtain mixed solution 1, then add starch to 0.5 mol / L hydrochloric acid, and stir in a constant temperature water bath at 60°C for 1 hour, adjust the pH to 4.0, then increase the temperature of the mixed solution to 70°C, add two-thirds of ammonium persulfate and stir and mix evenly, add mixed solution 1 dropwise, drip it for 1-2 hours, then add the remaining ammonium persulfate, react for 2-3 hours, and after the reaction is completed, obtain modified starch.

2. The degradable corrugated board glue according to claim 1, characterized in that: In step A1, the usage ratio of 5-aminoisophthalic acid, dimethylacetamide, triethylamine and acryloyl chloride is 0.2-0.4 mol: 50-150 mL: 7-21 mL: 0.2-0.4 mol.

3. The degradable corrugated board glue according to claim 1, characterized in that: The dosage ratio of starch, hydrochloric acid, ammonium persulfate and mixed solution 1 in step A2 is 3-6 g: 5.5-11 mL: 0.045-0.09 g: 1.5-3 mL, and the dosage ratio of sodium dodecyl sulfate, deionized water and product 1 in mixed solution 1 is 0.06-0.12 g: 15-30 mL: 0.25-0.45 g.

4. The degradable corrugated board glue according to claim 1, characterized in that: The starch includes any one of corn starch, wheat starch, tapioca starch and potato starch.

5. The degradable corrugated board glue according to claim 1, characterized in that: The modified flame retardant is prepared by the following steps: Step B1, add (3-aminopropyl)trimethoxysilane, triethylamine and diphenyl ether into a reactor, slowly add phenylphosphonic dichloride with a dropping funnel under nitrogen conditions, and always keep the system temperature ≤50°C. After the addition is completed, the system temperature is raised to 160-180°C for reaction for 4 hours. After the reaction is completed, filter with suction, then add water to dissolve the filter cake and adjust the pH to 8 under constant stirring, filter with suction again, wash, and vacuum dry at 80°C for 12 hours to obtain a flame retardant precursor; Step B2, under nitrogen conditions, add boric acid and 1,2-dichloroethane into a reactor, raise the temperature to 45-55°C and stir to mix evenly, then add the flame retardant precursor solution dropwise into the above reactor through a constant pressure dropping funnel, after the addition is completed, raise the temperature to 80-90°C and react for 7-9h, after the reaction is completed, filter the mixed solution, rotary evaporate the precipitate, and place the precipitate at 50°C under vacuum and dry for 12h to obtain a modified flame retardant.

6. The degradable corrugated board glue according to claim 5, characterized in that: In step B1, the usage ratio of (3-aminopropyl)trimethoxysilane, triethylamine, diphenyl ether and phenylphosphonic dichloride is 0.025-0.045 mol: 1.5-3.0 g: 50-100 mL: 0.01-0.02 mol.

7. The degradable corrugated board glue according to claim 5, characterized in that: In step B2, the amount ratio of boric acid, 1,2-dichloroethane and flame retardant precursor solution is 0.92-2.78g:20-60mL:30-90mL, and the flame retardant precursor solution is prepared by stirring and mixing the flame retardant precursor and 1,2-dichloroethane in an amount ratio of 7.19-21.56g:30-90mL.

8. The degradable corrugated board glue according to claim 1, characterized in that: The mass ratio of ethanol to deionized water in the ethanol solution is 8:

2.

9. The method for preparing the degradable corrugated board glue according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the raw materials by weight, stir acrylamidepropyltrimethoxysilane in an ethanol solution for 5 minutes to obtain a premix, then heat the modified starch to 60-70°C, and slowly add the premix and sodium hydroxide and stir to react for 30 minutes. After the reaction is completed, add the modified flame retardant, defoamer, plasticizer and stabilizer and stir to react for 30-60 minutes. After the reaction is completed, a degradable corrugated cardboard glue is obtained.

Citation Information

Patent Citations

  • Nano-modified starch adhesive for corrugated carton and preparation method of adhesive

    CN105440973A

  • Glue special for corrugated paperboards and preparation method of glue

    CN108003813A

  • Preparation method of high-strength quick-drying adhesive for corrugated case

    CN114163952A

  • Adhesive for manufacturing corrugated case and preparation method thereof

    CN116836648A